PENGARUH KUALITAS PELAYANAN, CITRA MEREK, KEPERCAYAAN DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN JASA BENGKEL LAS SINAR BARU DI JEPARA - Novertiza, Edda Christy Koes; Khasanah, Imroatul (Diponegoro Journal of Management, 2016)
The purpose of this study was to analyze the influence of service quality, brand image, trust and perception of price on purchase decisions. .The population in this study is a consumer transaction at the workshop "Sinar Baru", Jl. A. Yani 14, Jepara, Central Java. The sample in this study was 100 consumers. The sampling technique in this study was done by using purposive sampling. Is the primary data type. Methods of data collection using the questionnaire. The analysis technique used is multiple regression with previously tested with instruments and classical assumption. The results using multiple regression analysis showed that : Service quality influence on purchase decisions. Brand image influence on purchase decisions. Trust influence on e purchase decisions. Perception of Price influence the purchase decisions